The use of social grading in British market research - Meier, Erhard (Henry Stewart Talks, 2008)
Social Grading: a widely used classification system in the UK, the 'currency' for media planning and other marketing applications, Philosophy behind social grading, Concepts, Mechanics of social grading, Examples, Results: profile of adults in Great Britain, The discriminatory power of social grade, Main uses in market research, Criticism of social grade, Answer to criticism, Social grade, NS-SEC and the Census, Automated social grading, Conclusion